Freedom without restraint and responsibility: the problem of hate speech in Malaysia - Wan Mohd Nor, Murni; Mohd. Asraf, Ratnawati (LexisNexis, 2015)
Hate speech has been an issue of heated debate amongst legal scholars and human rights activists particularly between Western and Eastern countries. This is primarily due to the difference in our conceptions and prioritisation of rights. Freedom of speech is undoubtedly important due to the values it promotes, but too much emphasis on this right has resulted in the neglect of the due exercise of responsibility, often leading to, and perpetuating hate speech. While free speech should be protected, one should not disregard the preservation of public interest and peace within society. The authors argue that hate speech can be justifiably legislated, as it does not help in the attainment of free speech values. Then, the role of hate speech is spreading and reinforcing racism and discrimination are discussed. Focusing on Malaysia, the authors highlight the instances of racial and religious conflict and explain how hate speech aggravates race relations. Lastly, the authors propose a conception of human rights guided by religious values, which is especially important for multi-cultural and multi-religious countries. It is hoped that by considering the meaning and purpose of free speech in light of the problems caused by hate speech, there will be a better appreciation for the need to balance freedom of the individual with restraint and responsibility.